(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Influenza vaccination remains a vital preventive strategy, particularly in populations with comorbidities, yet its uptake is variable across different demographic groups. Understanding factors influencing vaccination can guide public health interventions. Objective: To assess the influenza vaccination coverage rates in high-risk patient groups. Methodology: This descriptive cross-sectional study was conducted among 190 adult participants. Data were collected using a structured questionnaire assessing demographic characteristics, comorbidities, vaccination status, and knowledge about influenza vaccination. Knowledge scores were categorized as poor (0–3), moderate (4–6), and good (7–9). Statistical analyses were performed using Chi-square tests, with a p-value ≤ 0.05 considered significant. Results: The mean age of participants was 54.6 ± 14.2 years, with 56.8% males. Most participants were married (75.8%), unemployed/retired (62.1%), and resided in urban areas (63.7%). Knowledge assessment revealed that 28.4% had poor knowledge, 48.4% moderate knowledge, and 23.2% good knowledge, with an overall mean score of 4.9 ± 2.1. Influenza vaccination was significantly associated with diabetes mellitus (p = 0.027), while higher vaccination rates were observed among individuals ≥50 years (p = 0.018), those with higher education (p = 0.004), and employed participants (p = 0.042). Gender did not show a significant association with vaccination status. Conclusion: Despite moderate knowledge levels, influenza vaccination coverage remains suboptimal. Comorbid conditions, education, age, and employment significantly influenced uptake. Targeted health education and vaccination campaigns are recommended to improve coverage, particularly among high-risk groups.